If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m = 7(7x + -1) Reorder the terms: 8m = 7(-1 + 7x) 8m = (-1 * 7 + 7x * 7) 8m = (-7 + 49x) Solving 8m = -7 + 49x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '8'. m = -0.875 + 6.125x Simplifying m = -0.875 + 6.125x
| 18.84=2(3.14) | | 0.3(32)+x=0.3(20+x) | | 11x+45=2x | | (5-6i)(3-2i)=0 | | 3q+10=7 | | 7-(6x+2)=(x-12)+3 | | 2a+9=5a-6 | | x=18-2/3 | | 6+x=54 | | 67-39= | | 9.4=x-17 | | 2a+9=5a+6 | | .05x+.10(19-x)=1.55 | | 27=.9(200-a) | | 2x+3m-5x+7m= | | -3y-9=6y+18 | | x-11+-7= | | 36(x-25)=1620 | | 6x=7.8 | | 10-5-2x=-4x-7 | | 10h-10=10 | | 36xsquared=1 | | 3-4(4b-1)=10b+6 | | 2n+2=-298 | | Y=cosh(ln(x)) | | 7t-6=-106 | | 2x+5y=-1fory | | 5k^2-3=2k | | 50x+19=-1431 | | 1-2n=9 | | p-1=7p-8 | | x+36=4z |